Causative Factors behind an Efficacious Teacher: Evaluating Teacher Efficacy - Batool Sadia; Mubarak Abbas Shah Syed (Journal of Human Psychology, 2018)
In the third world school dropout rates are the highest, which is largely attributable to a dearth of efficacious teachers. The present research is an analysis of the teacher efficacy based on the teaching milieu. The Ohio State Teacher Efficacy Scale was used for data collection. Probability sampling design was used to select 171 secondary school teachers. As per the results, subject specialization affects teacher efficacy the most whereas, institution type influences teacher efficacy the least. The less experienced teachers have a greater self-efficacy than the experienced teachers, teachers teaching uncrowded classes are more efficacious than those teaching crowded classes.
Keywords: Academic achievement